Commodity Price Characteristics And The Economics of Gold Price Movements - Modi, Shripal Alkesh (2011)
To understand the economics of daily gold price data for five years from 2006 to 2011, a linear regression log-log model is developed to establish the correlation relationship of some of the most relevant macro-economic variables affecting gold price. Empirical results showed predicted correlation relationships as in previous literature, and the high significance levels suggest that the movements of gold price is highly correlated with the drivers during a recession, thus suggesting that gold is considered as a crisis hedge. The demand and supply factors were also explored, alongside evaluating commodity and gold price characteristics of convenience yield and mean reversion. Finally, Monte-Carlo simulation using gBm was undertaken to simulate future gold price movements.